Pengembangan Sistem Informasi Kelompok Simpan Pinjam untuk Meningkatkan Efisiensi Manajemen Keuangan Komunitas - Yunita, Tuti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2022)
This research aims to develop and implement a Savings and Loan Group Information System to enhance the efficiency of financial management within community groups. The system is designed to automate and streamline the processes involved in managing savings, loans, and member contributions. Key features of the system include member registration, savings tracking, loan application and approval, repayment scheduling, and financial reporting. By integrating secure authentication and data encryption, the system ensures the safety and confidentiality of member information. The study discusses the design and development phases, including technology selection, system architecture, and user interface design. The system is evaluated based on its impact on operational efficiency, accuracy of financial records, and user satisfaction. The results indicate that the implementation of the Savings and Loan Group Information System leads to significant improvements in the management of financial activities, reducing administrative burden and enhancing transparency. Challenges encountered during the development and deployment phases are addressed, along with the solutions implemented to ensure successful adoption and integration.